An Innovative Aircraft Skin Damage Assessment Using You Only Look Once-Version9: A Real-Time Material Evaluation System for Remote Inspection - Kuo-Chien Liao; Jirayu Lau; Muhamad Hidayat (Aerospace)
Aircraft safety is the aviation industry’s primary concern. Inspections must be conducted before each flight to ensure the integrity of the aircraft. To meet the increasing demand for engineers, a system capable of detecting surface defects on aircraft was designed to reduce the workload of the inspection process. The system utilizes the real-time object detection capabilities of the you only look once-version 9 (YOLO v9) algorithm, combined with imagery captured from an unmanned aerial vehicle (UAV)-based aerial platform. This results in a system capable of detecting defects such as cracks and dents on the aircraft’s surface, even in areas that are difficult to reach, such as the upper surfaces of the wings or the higher parts of the fuselage. With the introduction of a Real-Time Messaging Protocol (RTMP) server, the results can be monitored via artificial intelligence (AI) and Internet of Things (IoT) devices in real time for further evaluation. The experimental results confirmed an effective recognition of defects, with a mean average precision (mAP@0.5) of 0.842 for all classes, the highest score being 0.938 for dents and the lowest value 0.733 for the paint-off class. This study demonstrates the potential for developing image detection technology with AI for the aviation industry.